FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH UNTUK MENABUNG TABUNGAN SIMAPAN DI BANK DAERAH LAMONGAN JAWA TIMUR - Sani Rusminah; Indira Shofia Maulida; Ike Susanti (JURNAL ILMIAH EDUNOMIKA, 2022)
This study is a survey research on Regions Bank Headquarters Lamongan with title "The Influence of Customer Decision to Save the Savings Simapan in Lamongan Regional Banks ". The purpose of this research is to find out and analyze if there is partial effect, simultaneous and dominant among the factors of interest, quality of service and gifts to the customer's decision to save. To determine the influence of the relationship between the variables used multiple regression analysis, t test and F test test data analysis using the SPSS version 17 with the results of (1) Y = 0.157 + 0.127 + 0.480 X1 + 0.396 X2 X3 + X2 E showed the most dominant variable ( 2) test the t interest (1,992), quality of service (5.314) and gifts (4.778), the value of t count> t table (1.986) means a partial effect on the dependent variable (3) F count (312 329)> F table 2,70 means the simultaneous effect on the dependent variable. The conclusion of this study is the variable of interest, quality of service and reward influence the customer's decision to save the savings Simapan in Lamongan Regional Banks.